Biometais como indutor de resistência no feijoeiro sobre Xanthomonas axonopodis pv. phaseoli e colletotrichum lindemuthianum - Queiroz, Samara Brandão (2019)
Among the factors that effect the produtivity, the plant diseases show a limiting potential, especially due the cost of control and environmental risks. The objective of this study was to evaluate the resistance-inducing effect of metalaminoacid chelates on control of common bacterial blight (Xanthomonas axonopodis pv. phaseoli) and anthracnose of common bean (Colletotrichum lindemuthianum). The experiments were carried out in vitro, in greenhouse and in the field, in two places (Marechal Cândido Rondon and Toledo - PR). In vitro condition, the fungitoxic effect of the metal-aminoacid chelates of Cu, Mn, Ca and Zn on spores of C. lindemuthianum and bactericide on X. axonopodis pv. phaseoli were evaluated. Both experiments were carried out in a completely randomized design, in factorial scheme (4x5) (four products in concentrations 0, 0.25, 0.5, 0.75 and 1% (v/v)), with five replicates. In greenhouse and in the field, the experiments were performed in randomized blocks, with the metal-aminoacid chelates described plus the control (water) and four replicates. The results of different concentrations were submitted to analysis of variance and of regression test, the field data were submitted to a joint analysis, and for the severity evaluations applied the formula of the area under the disease progress curve (AUDPC). In vitro results evidenced the influence of the products on the spores germination of C. lindemuthianum, superior to 90% of control, and for X. axonopodis pv. phaseoli, the Zn treatment presented bactericidal effect, reducing the percentage of formed colonies in 67%. For the evaluations of common bacterial blight, the lowest ABDPC with the metal-aminoacid chelates of Ca and Zn were observed in protected culture, and the enzymatic activities showed peaks of activity after the spraying of the products, with subsequent drop after inoculation of the bacterium, and in the field trials an increase in the number of pods per plant was observed with the Cu treatment. Tests with C. lindemuthianum revealed the lowest AUDPC through the Cu treatment, and enzymatic activities were activated after the supply of Ca treatment to phenylalanine ammonia-lyase, Mn to polyphenoloxidase and β-1,3 glucanase, reduving after inoculation of pathogen. The municipality of Toledo-PR was less favorable to the development of C. lindemuthianum, metalaminoacid chelates did not influence the AUDPC means, nor in the agronomic variables. Considering the in vitro antimicrobial effects, the decrease of AUDPC for both diseases, enzymatic activation after the products supply, followed by the decrease after inoculation, and the increase in the number of pods per plant, it was concluded that the chelates tested have potential as inductors of resistance to X. axonopodis pv. phaseoli and C. lindemuthianum in common bean.